2004
DOI: 10.1111/j.1469-7610.2004.t01-1-00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Bullied by siblings: association with peer victimisation and behaviour problems in Israeli lower secondary school children

Abstract: Intervention strategies directed at reducing bullying in school should take into account pupils' experiences of victimisation by siblings at home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
141
2
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 136 publications
(172 citation statements)
references
References 89 publications
25
141
2
4
Order By: Relevance
“…Where investigated, it appears that those who were both victims and bullies (sibling bully/victims) were at higher risk of behaviour problems than those who were only victimised. No increased risk was found for bullies 2 . In contrast, the UK survey of maltreatment found only increased mental distress (reported by the parents) in relation to sibling victimisation in children 0-9 years but not in the self-reports of adolescents or young adults 45 .…”
Section: Sibling Bullying and Emotional And Behaviour Problemsmentioning
confidence: 84%
See 3 more Smart Citations
“…Where investigated, it appears that those who were both victims and bullies (sibling bully/victims) were at higher risk of behaviour problems than those who were only victimised. No increased risk was found for bullies 2 . In contrast, the UK survey of maltreatment found only increased mental distress (reported by the parents) in relation to sibling victimisation in children 0-9 years but not in the self-reports of adolescents or young adults 45 .…”
Section: Sibling Bullying and Emotional And Behaviour Problemsmentioning
confidence: 84%
“…In the UK over 85% of adolescents have at least one sibling 1 ; in other regions it is normal for families to have several siblings 2 , with the largest offspring size found in sub-Saharan Africa 3 . There are exceptions, such as the China "One Child Policy (OCP)" which restricted the number of children that urban couples could have to one between 1979 and 2013 when it was relaxed 4 .…”
Section: Siblingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prevalence rates appear to differ according to type of aggression. Studies which assess multiple forms of aggression have found that victims most often report being physically or verbally victimized by their siblings; fewer experience teasing or psychological forms of aggression (Button & Gealt, 2010;Duncan, 1999;Skinner & Kowalski, 2013;Wolke & Samara, 2004). Using a child and adolescent sample, found that 32% had experienced physical victimization in the last year, while significantly fewer reported property-based (10%) or psychological victimization (3%).…”
Section: Definition and Prevalencementioning
confidence: 99%